Mechanics of solids and structures - Fenner, Roger T.; Reddy, J. N. [ (Junuthula Narasimha)] , 1945- (Computational mechanics and applied analysis, 2012)
"A revision of a popular textbook, this volume emphasizes the development of analysis techniques from basic principles for a broad range of practical problems, including simple structures, pressure vessels, beams and shafts. The book integrates numerical and computer techniques with programs for carrying out analyses, facilitating design, and solving the problems found at the end of each chapter. It also presents the underlying theory and traditional manual solution methods along with these techniques. This new second edition covers relationships between stress and strain, torsion, statically determinate systems, instability of struts and columns, and compatibility equations"-- Provided by publisher